x2 + 6x + 1 = 0
x2 + 6x + 9 = 8
(x + 3)2 = 8
x + 3 = ± 2√2
x + 3 = -3 ± 2√2
x ∈ {-3 - 2√2, -3 + 2√2}
Chat with our AI personalities
x2+6x-40 = 0 (x+10)(x-4) = 0 x = 4 or x = -10
x2 + 6x - 110 = 0 ∴ x2 + 6x = 110 ∴ x2 + 6x + 36 = 146 ∴ (x + 6)2 = 146 ∴ x + 6 = ±1461/2 ∴ x = -6 ±1461/2 ∴ x ≈ 6.083, 18.083
x2+6x+9 = x+3 x2+6x-x+9-3 = 0 x2+5x+6 = 0 Solve by factoring or with the help of the quadratic equation formula: (x+3)(x+2) = 0 Therefore: x = -3 or x = -2
x2 +6x = 27 x2 + 6x - 27 = 0 x2 + 9x - 3x - 27 = 0 x(x + 9) - 3(x + 9) =0 (x - 3)(x + 9) = 0 So x can equal 3 or -9.
No answer in integers. Quadratic formula gives roots as -1.268 and -4.732